An identification of dramatis personae distribution in Malaysian folktales for structural classification as a preservation means of Malaysian folktales - Harun, Harryizman; Jamaludin, Zulikha (Revista Tecnica De La Facultad De Ingenieria Universidad Del Zulia, 2016)
Malaysian folktales are one of the intangible cultural heritages that reflect and carry the lineage of the past generations to the present. It deserves to be preserved systematically but thus far; it is found such effort is scarce if not lacking in this country.Therefore, a study is conducted to preserve such valuable heritage through structural classification of the folktales.To achieve such classification, embedded narrative structures of the folktales are sought and utilized.Additionally, as a method to guide the analysis to excavate the narrative structures, 31 functions of folktale’s morphology are adapted. Even so, before the functions are acquired, the folktale’s dramatis personae and its spheres of action based on the morphology of folktale are utilized as methods to support in the identification of the functions.Atlas.ti, a computer-aided qualitative data analysis software (CAQDAS) is used to support the analysis of the folktales to obtain the dramatis personae and the functions because it increases the validity of the analysis conducted.To that end, this article presents the distribution of the dramatis personae identified to assist the classification process of the folktales and also the finding of the analysis implemented on the collected folktales which are the sequences of function that eventually form the structural classification.Academic paper: An Identification of Dramatis Personae Distribution in Malaysian Folktales for Structural Classification.